2019
DOI: 10.1097/gme.0000000000001210
|View full text |Cite
|
Sign up to set email alerts
|

Age and leptinemia association with anxiety and depression symptoms in overweight middle-aged women

Abstract: Objective: The aim of the study was to investigate the effect of menopause and of postmenopausal stages on depression and anxiety symptoms, and whether these symptoms associate with anthropometric, metabolic, and hormonal parameters in midlife women. Methods: Postmenopausal women (age 50-65), either at early (EPM, n=33) or late (LPM, n = 23) postmenopause, and 23 premenopausal controls (PreM, age 40-50), matched for BMI with the PM groups, were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 76 publications
3
14
0
Order By: Relevance
“…In relation to depressive-like behaviours, the ovariectomized rats showed the highest frequency of immobility and the shortest latency to immobility, features highly indicative of a depressive-like state 29 . The present results agree with previous demonstrations of induction of anxious-and depressive-related behaviours by ovariectomy in rodents 4,30 as well as of increased depression and anxiety rates in postmenopausal women 2,12 . Similarly, it has been reported, in both rats and mice, that estrogen replacement attenuated the increased immobility and decrease of active behaviours induced by ovariectomy 31 .…”
Section: Discussionsupporting
confidence: 93%
“…In relation to depressive-like behaviours, the ovariectomized rats showed the highest frequency of immobility and the shortest latency to immobility, features highly indicative of a depressive-like state 29 . The present results agree with previous demonstrations of induction of anxious-and depressive-related behaviours by ovariectomy in rodents 4,30 as well as of increased depression and anxiety rates in postmenopausal women 2,12 . Similarly, it has been reported, in both rats and mice, that estrogen replacement attenuated the increased immobility and decrease of active behaviours induced by ovariectomy 31 .…”
Section: Discussionsupporting
confidence: 93%
“…One study found no difference in leptin levels between children with anxiety disorders and controls (78). In adult participants, low cerebrospinal fluid (CSF) leptin in females who recently attempted suicide was associated with higher anxiety, while patients who had moderate to severe anxiety had a higher free leptin index, and leptin was positively associated with anxiety in overweight women (43,79,80). Our results add to this literature by suggesting that genetic variation at LEPR may play a role in anxiety disorders.…”
Section: Discussionsupporting
confidence: 50%
“…Future studies should consider larger samples and longitudinal assessments to better understand and explain this relationship. Finally, regarding anxiety, heterogeneous results on its relationship with both weight status [ 43 , 44 ] and BP [ 12 , 45 ] have been reported in previous studies. Regarding BP, a meta-analysis by Pan et al [ 4 ] showed that studies had found anxiety symptoms to be an independent risk factor for hypertension.…”
Section: Discussionmentioning
confidence: 99%